Measuring inequality of opportunity across EU-SILC countries : national and urban-rural perspectives - Mogila, Zbigniew (2020)
Inequality in individuals’ outcomes resulting from unequal access to opportunities due to differences in individual circumstances, such as family background and/or race, are generally considered to be unfair and ethically unacceptable. Since wealthier individuals and their families tend to live in more affluent areas and mingle with similar more affluent peers, the territorial distribution of inequality of opportunity may partially be viewed as a measure of the extent of spatial (in)justice. One of the ways governments can use to mitigate inequality of opportunity is to improve access to socially valued resources, e.g. education, health. If the spatial distribution of these resources is not equitable, or prevents equitable access to them, persistent or even growing differences in inequality of opportunity may arise. Improving the spatial distribution of socially valued resources can help individuals enhance their socioeconomic prospects, while also increasing the full utilization of territorial capital and, consequently, contribute to greater socioeconomic cohesion. This paper measures the extent of inequality of opportunity at the national level and by degree of urbanization for the countries covered in the survey European Union Statistics on Income and Living Conditions (EU-SILC). Emphasis on the degree of urbanization allows exploring whether large(r) cities can act as social elevators compared to smaller urban and rural areas. Using the EUSILC data, we implement regression models to measure the percentage of the variation in individual’s labour income that is due to family background, namely, the education, occupation and activity status of parents, and household financial situation. Our results indicate substantial variation in inequality of opportunity ranging from 4% (Iceland) to 25% (Luxemburg). In addition, the distinction between more liberal economies and the rest of the countries is seen with the former more income unequal, however, with the smaller impact of family-related factors on individual’s income. Moreover, the findings suggest that cities, especially larger ones, do not seem to work as social elevators and may in fact benefit individuals with a better family background.